Optimizing Microalgae Diet, Temperature, and Salinity for Dwarf Surf Clam, Mulinia lateralis, Spat Culture - Yang, Zujing; Wang, Hao; Li, Moli; Teng, Mingxuan; Wang, Xuefeng; Zhao, Ang; Huang, Xiaoting; Hu, Jingjie; Bao, Zhenmin (Frontiers in Marine Science, 2022)
Dwarf surf clam, Mulinia lateralis, is widely considered as a model species for bivalves. The development of a standard culture system could greatly promote the production of high-quality individuals, yet information on the culture conditions for M. lateralis spat is still limited. This study aims to determine the suitable microalgae diet, temperature, and salinity for M. lateralis spat culture. The typically fed microalgae species, including Chlorella pyrenoidesa (Cp), Platymonas helgolandica (Ph), Dunaliella salina (Ds), Nitzschia closterium (Nc), and Chaetoceros muelleri (Cm), could be taken up by M. lateralis spat, and their filtration rates on Cp, Nc, and Cm were higher than those on Ds and Ph. For the entire spat culture, all diet trials showed similar survival percentages, while the mono-specific diet Cp exhibited the highest growth rate, suggesting that Cp was the optimal microalgae species for M. lateralis spat. Through simultaneously maximizing the growth and survival of spat, the optimal microalgae concentration and stocking density were 5 × 104 cells ml–1 and 400–600 individuals m–2 for 30–40-day-old spat as well as 1 × 105 cells ml–1 and 400–600 individuals m–2 for 40–50-day-old spat, respectively. In addition, the spat had higher growth rates and survival percentages at the temperature of 20–22°C and salinity of 22–25 ppt. The results of this study provide a basis for further culture of M. lateralis spat, and the optimized conditions will be of great significance for the construction of the standard culture system of M. lateralis.